Global Transcriptomic Analysis of Bacteriophage-Host Interactions between a Kayvirus Therapeutic Phage and Staphylococcus aureus - Finstrlová, Adéla; Mašlaňová, Ivana; Blasdel Reuter, Bob G; Doškař, Jiří; Götz, Friedrich; Pantůček, Roman (Microbiology spectrum, 2022)
Kayviruses are polyvalent broad host range staphylococcal phages with a potential to combat staphylococcal infections. However, the implementation of rational phage therapy in medicine requires a thorough understanding of the interactions between bacteriophages and pathogens at omics level. To evaluate the effect of a phage used in therapy on its host bacterium, we performed differential transcriptomic analysis by RNA-Seq from bacteriophage K of genus Kayvirus infecting two Staphylococcus aureus strains, prophage-less strain SH1000 and quadruple lysogenic strain Newman. The temporal transcriptional profile of phage K was comparable in both strains except for a few loci encoding hypothetical proteins. Stranded sequencing revealed transcription of phage noncoding RNAs that may play a role in the regulation of phage and host gene expression. The transcriptional response of S. aureus to phage K infection resembles a general stress response with differential expression of genes involved in a DNA damage response. The host transcriptional changes involved upregulation of nucleotide, amino acid and energy synthesis and transporter genes and downregulation of host transcription factors. The interaction of phage K with variable genetic elements of the host showed slight upregulation of gene expression of prophage integrases and antirepressors. The virulence genes involved in adhesion and immune evasion were only marginally affected, making phage K suitable for therapy. IMPORTANCE Bacterium Staphylococcus aureus is a common human and veterinary pathogen that causes mild to life-threatening infections. As strains of S. aureus are becoming increasingly resistant to multiple antibiotics, the need to search for new therapeutics is urgent. A promising alternative to antibiotic treatment of staphylococcal infections is a phage therapy using lytic phages from the genus Kayvirus. Here, we present a comprehensive view on the phage-bacterium interactions on transcriptomic level that improves the knowledge of molecular mechanisms underlying the Kayvirus lytic action. The results will ensure safer usage of the phage therapeutics and may also serve as a basis for the development of new antibacterial strategies.
Keywords: Staphylococcal Infections; Staphylococcus aureus; Staphylococcus Phages; transcriptome; Humans; Staphylococcus phages; stafylokokové bakteriofágy; stafylokokové infekce; Kayvirus; profágy; lidé; bacteriophage therapy; viral transcription; prophages; RNA-Seq; transkriptom; Transcriptome; Prophages; phage-host interactions; noncoding RNA